+0  
 
0
77
1
avatar

Simply sqrt(20) + sqrt(45) + sqrt(80) - 2*sqrt(125) + 1/(sqrt(5) - 2).

 May 13, 2020
 #1
avatar+21953 
0

sqrt(20)  =  sqrt(4·5)  =  sqrt(4)·sqrt(5)  =  2sqrt(5)

sqrt(45)  =  sqrt(9·5)  =  sqrt(9)·sqrt(5)  =  3sqrt(5)

sqrt(80)  =  sqrt(16·5)  =  sqrt(16)·sqrt(5)  =  4sqrt(5)

2·sqrt(125)  =  2·sqrt(25·5)  =  2·sqrt(25)·sqrt(5)  =  2·5·sqrt(5)  =  10sqrt(5)

1 / [sqrt(5) - 2] · [sqrt(5) + 2] / [sqrt(5) + 2]  =  [sqrt(5) + 2] / [5 - 4]  =  sqrt(5) + 2

 

     sqrt(20) + sqrt(45) + sqrt(80) - 2·sqrt(125) + 1 / [sqrt(5) - 2]

 

=  2sqrt(5) + 3sqrt(5) + 4sqrt(5) - 10sqrt(5)     + [ sqrt(5) + 2 ]     =     2

 May 13, 2020

44 Online Users

avatar